2017
DOI: 10.1007/s00277-017-3194-4
|View full text |Cite
|
Sign up to set email alerts
|

Between a rux and a hard place: evaluating salvage treatment and outcomes in myelofibrosis after ruxolitinib discontinuation

Abstract: Ruxolitinib is a JAK1/2 inhibitor that is effective in managing symptoms and splenomegaly related to myelofibrosis (MF). Unfortunately, many patients must discontinue ruxolitinib, at which time treatment options are not well defined. In this study, we investigated salvage treatment options and clinical outcomes among MF patients who received and discontinued ruxolitinib outside the context of a clinical trial. Among 145 patients who received ruxolitinib, 23 died while on treatment, 58 remained on treatment at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 20 publications
5
111
0
Order By: Relevance
“…13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib. 21 Here, we report the outcome of 218 patients after ruxolitinib.…”
Section: Introductionmentioning
confidence: 99%
“…13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib. 21 Here, we report the outcome of 218 patients after ruxolitinib.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is limited evidence to show that ruxolitinib improves survival outcomes by modifying the disease course, although its effect on metabolic and nutritional variables may translate into survival benefits. 9 Eventually, most patients discontinue treatment due to adverse events or lack of efficacy. 9 In recent phase-III studies, about 50% of patients discontinued ruxolitinib within 3 years of treatment.…”
mentioning
confidence: 99%
“…9 Eventually, most patients discontinue treatment due to adverse events or lack of efficacy. 9 In recent phase-III studies, about 50% of patients discontinued ruxolitinib within 3 years of treatment. 7 Salvage therapy options remain scarce 10 and mostly include allogeneic stem cell transplantation (allo-SCT) followed by immunomodulators; however, prognosis is unfavourable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…62,63 Figure 5 in a qualified success with significant symptomatic benefit, but neither major change in the natural history nor a significant impact on the JAK2 V617F allelic burden, and a median survival of patients discontinuing ruxolitinib of 13-14 months. [67][68][69] The majority of other Type 1 JAK2 inhibitors have had their clinical development discontinued largely due to the emergence of serious neurotoxicity.…”
Section: Sm In the Midostaurin Eramentioning
confidence: 99%